Cyclophilin effector Al106 of mirid bug Apolygus lucorum inhibits plant immunity and promotes insect feeding by targeting PUB33. Issue 6 (29th December 2022) - Dong, Yumei; Zhou, Jiangxuan; Yang, Yuxia; Lu, Wangshan; Jin, Yan; Huang, Xingge; Zhang, Wendan; Li, Jifen; Ai, Gan; Yin, Zhiyuan; Shen, Danyu; Jing, Maofeng; et al.
Summary: Apolygus lucorum (Meyer‐Dur; Heteroptera: Miridae) is a major agricultural pest infesting crops, vegetables, and fruit trees. During feeding, A. lucorum secretes a plethora of effectors into its hosts to promote infestation. However, the molecular mechanisms of these effectors manipulating plant immunity are largely unknown. Here, we investigated the molecular mechanism underlying the effector Al106 manipulation of plant–insect interaction by RNA interference, electrical penetration graph, insect and pathogen bioassays, protein–protein interaction studies, and protein ubiquitination experiment. Expression of Al106 in Nicotiana benthamiana inhibits pathogen‐associated molecular pattern‐induced cell death and reactive oxygen species burst, and promotes insect feeding and plant pathogen infection. In addition, peptidyl‐prolyl cis‐trans isomerase (PPIase) activity of Al106 is required for its function to inhibit PTI.Al106 interacts with a plant U‐box (PUB) protein, PUB33, from N. benthamiana and Arabidopsis thaliana . We also demonstrated that PUB33 is a positive regulator of plant immunity. Furthermore, an in vivo assay revealed that Al106 inhibits ubiquitination of NbPUB33 depending on PPIase activity. Our findings revealed that a novel cyclophilin effector may interact with plant PUB33 to suppress plant immunity and facilitate insect feeding in a PPIase activity‐dependent manner.